STRATEGI PENINGKATAN KESIAPAN KERJA LULUSAN PERGURUAN TINGGI DI ERA PASAR BEBAS - F. Winarni F. Winarni (Jurnal Cakrawala Pendidikan, 2002)
Indonesia's involvement in the eraof economic globalization has brought about the consequenceof participating inthe ratificationof the WTO agreement known as the MarrakechDeclaration, which concerns the principles enforced in the freetrade. Along with industrial developments, there have come intoexistence various occupation andjobqualifications requiring newskills and expertise to support scientific and technologicaldevelopments. As a further consequence, there would occur ashift in work values in company management. In the aspectofmanufacturing activity, there would be a shift from high-volumeto high-value production.To anticipatejob market needs with a view on the reality ofthe quality ofour education, it is necessary to prepare a suitablestrategy in developing human resources through education andtraining. With the newly-available opportunities as pointsof departure, universities as agents of improvement should be abletoproduce a work force not only skilful but also of highintelligence, profound reliability, and strong personality in. order to be able to compete abroad. There need to be effortsto implement in any process in the education and training involving communication of.infannation and teaching-learninginteraction a strategy incorporating a dynamic and dialogicatmosphere